Somatic Rights of Minors: The Intersection of Law and Ethics in the Legal System of Uzbekistan - Saidkomilova , Sevinchoy (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article examines the somatic rights of minors, specifically their legal ability to exercise control over their own bodies, to give or refuse consent to medical interventions. The author analyzes this issue from both legal and bioethical perspectives, drawing a comparative analysis between international practices and the legal framework of Uzbekistan. Key topics such as minor consent, the role of parents or legal guardians, medical coercion, and legal capacity are thoroughly explored. The study identifies existing legal gaps and normative challenges in Uzbekistan's current system and offers practical recommendations to enhance the protection of minors' somatic rights.